Designing places for people and the environment : lessons from 55 years as an urban planner and shaping the global landscape architectural practice of the SWA Group - Platt, Kalvin (2014)
Part autobiography, part firm history and part a look at the future of urban design, [this book] addresses lessons learned from fifty five years of experience in urban design and planning from a personal perspective following the author s formative education and work as an architect, Naval civil engineer and city planner before transitioning into landscape architecture where he grew into a leadership role as the first president of the SWA Group and shaped the firm as an employee owned group practice that over four decades has become a world leader in landscape architecture, planning and urban design . More than just a monograph, the book relates important developments in the firm and profession to major world events of the late 20th and early 21st centuries, using 35 case studies of his major work and portfolios of the firms iconic work over its entire history to date, and a best practices section detailing how the firm has developed business and professional practices that allow it to focus upon its people and work: planning, designing and building livable and environmentally sustainable cities and communities where people can live in dignity, health and happiness.
Keywords: Platt, Kalvin; Platt, Kalvin; SWA Group (Firm); SWA Group (Firm); SWA Group (Firm); City planning; City planning; City planning